1996
DOI: 10.2337/diacare.19.11.1207
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Fish Oil on Insulin Resistance and Plasma Lipoproteins in NIDDM Patients With Hypertriglyceridemia

Abstract: In NIDDM patients with hypertriglyceridemia, moderate amounts of fish oil induce a long-term significant reduction in plasma triglycerides, VLDL triglycerides, and NEFA and a significant enrichment in the erythrocyte phospholipid content of long-chain omega-3 fatty acids, without deteriorating blood glucose control. However, this amount of omega-3 fatty acids was unable to improve insulin sensitivity in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(68 citation statements)
references
References 0 publications
2
66
0
Order By: Relevance
“…The trials included in the pooled analyses were small, with a median of 23 patients. Seventeen of the published papers were duplicate publications of six trials [22, 27, 33, 34, 36-38, 40, 42-46, 48, 51, 54, 55]; multiple papers for each trial are indicated by the following grouping of references: [22,38], [27,34,36,37], [40,54,55], [42,48,51], [43,46], [44,45]. There was sufficient information on only 12 of the 98 outcomes to allow data to be pooled, the results of which are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The trials included in the pooled analyses were small, with a median of 23 patients. Seventeen of the published papers were duplicate publications of six trials [22, 27, 33, 34, 36-38, 40, 42-46, 48, 51, 54, 55]; multiple papers for each trial are indicated by the following grouping of references: [22,38], [27,34,36,37], [40,54,55], [42,48,51], [43,46], [44,45]. There was sufficient information on only 12 of the 98 outcomes to allow data to be pooled, the results of which are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The trials reporting HLD-2 and HDL-3 were of 8 weeks duration or less. Three trials reported changes in HDL-TG among 80 non-hypertriacylglycerolaemic subjects [34,47,48]. n-3 PUFA non-significantly decreased HDL-TG by 0.01 mmol/l (95% CI −0.05 to 0.03; p=0.65) (ESM Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations